Pengaruh Media Exposure, Sensitivitas Industri, Kepemilikan Asing, Kepemilikan Publik dan Profitabilitas Terhadap Environmental Disclosure dan Dampaknya Terhadap Nilai Perusahaan - Farida Julekhah; Evi Rahmawati (Reviu Akuntansi dan Bisnis Indonesia, 2019)
This study aims to determine how the influence of media exposure, industry sensitivity, foreign ownership, public ownership and profitability on environmental disclosure and the impact on firm value. The subjects in this study were mining, energy, chemicals, pharmaceuticals, cosmetics, food and beverage companies listed on the Indonesian Stocks Exchange in 2016-2017. The research sample was determined using purposive sampling. This study has a sample of 35 companies with a total of 70 data processed. Data was processed using the IBM SPSS 22 statistical program and analyzed using multiple regression for the first research model and simple regression for the second research model. Based on the results of data analysis, it is known that only industry sensitivity and public ownership variables have a positive effect on environmental disclosure. Meanwhile, media exposure, foreign ownership, profitability do not affect the environmental disclosure, and environmental disclosure variable do not affet the firm value.